Pmp Repertoires Influence the Different Infectious Potential of Avian and Mammalian Chlamydia psittaci Strains - Favaroni, Alison; Trinks, Alexander; Weber, Michael; Hegemann, Johannes H.; Schnee, Christiane (Frontiers in Microbiology, 2021)
Chlamydia (C.) psittaci is the etiological agent of chlamydiosis in birds and can be transmitted to humans, causing severe systemic disease. C. psittaci infects a broad range of hosts; strains are isolated not only from birds but also from mammals, where they seem to have a reduced infectious and zoonotic potential. Comparative analysis of chlamydial genomes revealed the coding sequences of polymorphic membrane proteins (Pmps) to be highly variable regions. Pmps are characterized as adhesins in C. trachomatis and C. pneumoniae and are immunoreactive proteins in several Chlamydia species. Thus, Pmps are considered to be associated with tissue tropism and pathogenicity. C. psittaci harbors 21 Pmps. We hypothesize that the different infectious potential and host tropism of avian and mammalian C. psittaci strains is dependent on differences in their Pmp repertoires. In this study, we experimentally confirmed the different virulence of avian and mammalian strains, by testing the survival rate of infected embryonated eggs and chlamydiae dissemination in the embryos. Further, we investigated the possible involvement of Pmps in host tropism. Analysis of pmp sequences from ten C. psittaci strains confirmed a high degree of variation, but no correlation with host tropism was identified. However, comparison of Pmp expression profiles from different strains showed that Pmps of the G group are the most variably expressed, also among avian and mammalian strains. To investigate their functions, selected Pmps were recombinantly produced from one avian and one mammalian representative strain and their adhesion abilities and relevance for the infection of C. psittaci strains in avian and mammalian cells were tested. For the first time, we identified Pmp22D, Pmp8G and OmcB as relevant adhesins, essential during infection of C. psittaci strains in general. Moreover, we propose Pmp17G as a possible key player for host adaptation, as it could only bind to and influence the infection in avian cells, but it had no relevant impact towards infection in mammalian cells. These data support the hypothesis that distinct Pmp repertoires in combination with specific host factors may contribute to host tropism of C. psittaci strains.